APPLICATION OF UREA-FORMALDEHYDE AND UREA-FURFURAL RESINS IN DIFFERENT SOLVENTS - Jamilova Niginabonu Qobil qizi; Nasilloyev Dilshodbek Davron o’g’li (American Journals, 2023)
The article presents a study on the production synthesized resins are soluble in xylene, dioxane and sulfides and are insoluble in water. Cleaning resins from various additives to obtain high-quality varnish, enamel, glue and paints.
Keywords: dioxane, sulfide, varnish, enamel, glue, furan paints, furfuryl alcohol, sodium hydroxide.